Enabling High‐Performance Tandem Organic Photovoltaic Cells by Balancing the Front and Rear Subcells. Issue 38 (16th August 2020) - Cheng, Pei; Wang, Hao‐Cheng; Zheng, Ran; Zhu, Yuan; Dai, Shuixing; Li, Zeyuan; Chen, Chung‐Hao; Zhao, Yepin; Wang, Rui; Meng, Dong; Zhu, Chenhui; Wei, Kung‐Hwa; et al.
Abstract: In tandem organic photovoltaics, the front subcell is based on large‐bandgap materials, whereas the case of the rear subcell is more complicated. The rear subcell is generally composed of a narrow‐bandgap acceptor for infrared absorption but a large‐bandgap donor to realize a high open‐circuit voltage. Unfortunately, most of the ultraviolet–visible part of the photons are absorbed by the front subcell; as a result, in the rear subcell, the number of excitons generated on large‐bandgap donors will be reduced significantly. This reduces the (photo) conductivity and finally limits the hole‐transporting property of the rear subcell. In this work, a simple and effective way is proposed to resolve this critical issue. To ensure sufficient photogenerated holes in the rear subcell, a small amount of an infrared‐absorbing polymer donor as a third component is introduced, which provides a second hole‐generation and transporting mechanism to minimize the aforementioned detrimental effects. Finally, the short‐circuit current density of the two‐terminal tandem organic photovoltaic is significantly enhanced from 10.3 to 11.7 mA cm −2 (while retaining the open‐circuit voltage and fill factor) to result in an enhanced power conversion efficiency of 15.1%. Abstract : In tandem organic photovoltaics, most ultraviolet–visible photons are absorbed by the front sub‐cell, so in the rear sub‐cell, excitons generated on large‐bandgap donors will be reduced significantly. This reduces the conductivity and limits the hole‐transporting property of the rear sub‐cell. An infrared‐absorbing polymer donor is introduced, which provides a second hole‐generation/transporting mechanism to minimize the aforementioned detrimental effects.